KOMUNIKASI PUBLIK DISKOMINFO KOTA BOGOR DALAM MENDUKUNG CAMPAIGN PENERTIBAN ANGKUTAN KOTA MELALUI MEDIA INSTAGRAM - Puja Tania, Sherly; Muljono, Pudji; Fuad Cholagi, Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the varied public responses to the urban public transportation regulation policy, which indicate challenges in government public communication. This condition requires an effective communication strategy so that policy information can be properly understood and accepted by the public. This study aims to identify the forms of public communication and to analyze the communication strategies employed by the Bogor City Diskominfo in supporting the campaign for urban public transportation regulation. The research uses a qualitative descriptive approach, with data collected through interviews, observation, and literature review. The findings show that public communication is carried out through the use of digital media, particularly Instagram, as the main channel for disseminating information. The communication is delivered through visual content such as infographics and videos designed to be easily understood and engaging for the audience. The communication strategy is structured systematically through stages of situation analysis, target audience identification, message formulation, media selection, and evaluation. Message delivery is designed to be concise, clear, and focused on the benefits for the public. Video-based content is found to be more effective than infographics in enhancing audience understanding and engagement. Public responses to the campaign remain varied and indicate challenges related to message clarity and information consistency. These findings suggest that well-planned and adaptive public communication is necessary to improve the effectiveness of policy dissemination and to encourage public participation.